2022
DOI: 10.2147/copd.s339889
|View full text |Cite
|
Sign up to set email alerts
|

Blood Eosinophils in Chinese COPD Participants and Response to Treatment with Combination Low-Dose Theophylline and Prednisone: A Post-Hoc Analysis of the TASCS Trial

Abstract: Background and Objectives:The burden of chronic obstructive pulmonary disease (COPD) disproportionately affects patients in low to middle-income countries. Although the Theophylline and Steroids in COPD Study (TASCS) showed no clinical benefit from administering low-dose theophylline and prednisone in COPD patients compared to placebo, it was hypothesized that those with elevated blood eosinophil counts would receive clinical benefit from the intervention. Methods: This was a post-hoc analysis of the TASCS dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(42 reference statements)
1
0
0
Order By: Relevance
“…The study group showed an incidence of adverse events of 14.75 %, which was slightly but not significantly higher than the 13.11 % rate of adverse events in the control group. Consistent with similar local and international studies, our results showed that combination treatment with theophylline sustained-release tablets and thymalfasin was effective in the treatment of COPD with respiratory failure [14,15]. It has been reported that sICAM-1, PGE2, and hs-CRP are clinically serum inflammatory factors [16,17].…”
Section: Trop J Pharm Res January 2023; 22(1): 170supporting
confidence: 90%
“…The study group showed an incidence of adverse events of 14.75 %, which was slightly but not significantly higher than the 13.11 % rate of adverse events in the control group. Consistent with similar local and international studies, our results showed that combination treatment with theophylline sustained-release tablets and thymalfasin was effective in the treatment of COPD with respiratory failure [14,15]. It has been reported that sICAM-1, PGE2, and hs-CRP are clinically serum inflammatory factors [16,17].…”
Section: Trop J Pharm Res January 2023; 22(1): 170supporting
confidence: 90%